2014
DOI: 10.1002/ccd.25751
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dilation atrial septostomy for advanced pulmonary hypertension in patients on prostanoid therapy

Abstract: BDAS may be an alternate therapy for select PH patients who have symptomatic progression despite prostanoid therapy. Survival is comparable to prior reports of BDAS in the pre-prostanoid era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Contraindications to AS include end-stage disease with right atrial pressure >20 mm Hg and O2 saturation <85% on room air [ 1 ]. Multiple authors reported high peri-procedural mortality in this category of patients [ 5 , 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraindications to AS include end-stage disease with right atrial pressure >20 mm Hg and O2 saturation <85% on room air [ 1 ]. Multiple authors reported high peri-procedural mortality in this category of patients [ 5 , 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique cannot be considered to be a well-established procedure because of controversial results and relatively small clinical experience. Experience with stent fenestratration of the atrial septum is very limited and does not exceed 15 interventions at one particular institution [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Technical expertise and experience with the procedure also contribute to mortality, as reflected by lower mortality reported in recent series. 22,23,29 The hemodynamic effects of an atrial septostomy depend highly on the baseline RAP. Table 1 shows how a higher baseline RAP will result in a more pronounced hemodynamic effect, particularly when RAP is Ͼ20 mm Hg (ie, severe RVF).…”
Section: Methodsmentioning
confidence: 99%
“…Ballon atrial septostomy is a known method used as a bridge to lung transplantation (LuTX) in patients with severe PAH and right ventricular failure with elevated right atrial pressure, however it may also be used as a palliative treatment for patients disqualified from LuTX to prolong their lives [4,5]. In the described case, such a reduction of right atrial pressure and sympathetic overactivity by the means of BAS [6] not only fulfilled the abovementioned role, but also showed another benefit -a relief from atrial tachycardia, which improved the patient's short-term prognosis [2,3].…”
Section: Balloon Atrial Septostomy In Pulmonarymentioning
confidence: 99%